1991
DOI: 10.1093/oxfordjournals.aje.a115926
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Cancer and Age at Last Delivery: Evidence for an Association

Abstract: Because the role hormonal and reproductive factors play in the etiology of endometrial cancer is incompletely understood, the authors evaluated the risk of this cancer in relation to age at last delivery. The data were obtained in a hospital-based case-control study of 483 women with endometrial cancer (cases) and 693 women with other conditions (controls) conducted in a number of hospitals in the United States and Canada from 1978 to 1985. There was an inverse association between age at last delivery and endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
25
1
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 0 publications
7
25
1
1
Order By: Relevance
“…This includes oral contraceptives, a recognised protective factor for endometrial cancer, and an exposure that would undoubtedly be more prevalent among subjects with late ages at first birth. This was not an important confounder in our study, given low rates of usage among Polish women, but other studies that have adjusted for oral contraceptives have shown a persistent effect of ages at last birth (Lesko et al, 1991;Parazzini et al, 1998). It seems more likely that differing analytic techniques may explain study discrepancies, as an analysis that appropriately accounted for correlated variables also did not confirm an effect of late ages at a last birth .…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…This includes oral contraceptives, a recognised protective factor for endometrial cancer, and an exposure that would undoubtedly be more prevalent among subjects with late ages at first birth. This was not an important confounder in our study, given low rates of usage among Polish women, but other studies that have adjusted for oral contraceptives have shown a persistent effect of ages at last birth (Lesko et al, 1991;Parazzini et al, 1998). It seems more likely that differing analytic techniques may explain study discrepancies, as an analysis that appropriately accounted for correlated variables also did not confirm an effect of late ages at a last birth .…”
Section: Discussionmentioning
confidence: 53%
“…We used a modelling approach ) that enabled combining data from parous and nulliparous women to separately evaluate effects of different parameters. We were particularly interested in following up the observations of an inverse relationship of endometrial cancer risk with ages at (Kvale et al, 1988;Lesko et al, 1991;Parazzini et al, 1991Parazzini et al, , 1998Lambe et al, 1999) and intervals since (Albrektsen et al, 1995;Parazzini et al, 1998) a last birth. Our results, like others (Shu et al, 1991;McPherson et al, 1996;Albrektsen et al, 1999), provide little support for these relationships.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have found an inverse association between older age at last birth and corpus uteri cancer risk, [39][40][41] hypothesised to be due to mechanical shedding of cells that have undergone malignant transformation in women when they give birth. 42 Further, it appears that the association is stronger in women aged below 50 years than in women over 50.…”
Section: Discussionmentioning
confidence: 99%